Current status and prospects of surrounding rock control and intelligent coal drawing technology in fully mechanized caving face - PANG Yihui; GUAN Shufang; JIANG Zhigang; BAI Yun; LI Peng (Gong-kuang zidonghua)
This paper analyzes the current status and existing issues in the control technology of surrounding rock and intelligent top coal caving technology for thick and ultra-thick coal seams in fully mechanized caving faces. The study focuses on five aspects: efficient support of roadway surrounding rock, advanced support of working faces, the caving behavior of hard ultra-thick top coal, hydraulic support position monitoring, and intelligent top coal caving. To tackle the technical challenges and engineering demands for safe, efficient, and intelligent caving mining, research was conducted on surrounding rock control technology and intelligent coal caving technology. A mechanical model for cantilever beams of hard ultra-thick top coal was developed, and key technologies to enhance caving characteristics and extraction rate of top coal were created, facilitating large-height caving mining of hard ultra-thick coal seams. A modular advanced hydraulic support with a rotating self-resetting device was developed, allowing the hydraulic support's beam to automatically rotate based on the inclination angle of the roadway roof, significantly improving its adaptability to the roof and floor of roadway. The idea of replacing traditional bolt-mesh support with hydraulic supports for roadway support was proposed, offering high support efficiency, low cost, and savings on advanced support. A monitoring device and algorithm for the support posture of fully mechanized caving hydraulic supports based on the stroke of the jacks of columns and tail beams were developed, enhancing calculation efficiency and accuracy. An intelligent coal drawing control method integrating transparent geological models, coal volume monitoring devices, and coal and gangue identification devices was proposed, effectively addressing the challenges of intelligent coal drawing from ultra-thick top coal with multi-gangue layers. The paper concludes that trends in intelligent fully mechanized caving mining technology and equipment include intelligent geological assurance technology, precise measurement and intelligent sensing via machine vision, adaptive control technology for fully mechanized caving mining equipment, and digital twin technology.